The development of a reliable and valid instrument to measure the osteoporosis-related knowledge: validation of the Hungarian version of Osteoporosis Knowledge Assessment Tool (OKAT) - Peter Tardi; Brigitta Szilagyi; Alexandra Makai; Monika Gyuro; Pongrac Acs; Melinda Jaromi; Balint Molics; Marta Hock (BMC, 2021)
Abstract Background Osteoporosis is one of the most common chronic musculoskeletal diseases. Osteoporosis-related knowledge is an important contributor in to prevent osteoporosis. There is no validated reliable questionnaire to measure the knowledge in Hungary. The aim of the study was to validate the Osteoporosis Knowledge Assessment Tool (OKAT) Hungarian version. Methods The research was a randomized validation study of a new Hungarian language instrument. The questionnaire was administered to 557 randomly selected healthy women (age between 25 and 44 years) from December 2018 to July 2019 in Baranya county, Hungary. The reliability was examined by the Flesch reading ease and McNemar's test. We examined item discrimination and item-total correlations, inter-item consistency (Cronbach's alpha coefficient) and principal component factor analysis. Results Significant differences (p <  0.001) were reported between total scores and the age categories. Significant (p <  0.001) correlation (r = 0.25) was found between the education level and the knowledge. Significantly (p <  0.001) higher knowledge were found in health care profession (14.53 ± 3.58) than the non-health care profession (9.99 ± 4.04). Participants with osteoporosis or fracture in family history had better knowledge (p <  0.001). Flesch reading ease was 44, the questionnaire had a Ferguson's sigma of 0.94 and a Cronbach's alpha of 0.81. There were no negative inter-item correlations psychometric properties of the OKAT, all items had more than 70% of correlations (p <  0.001). Conclusions The Hungarian version of the Osteoporosis Knowledge Assessment Tool is a reliable and objective questionnaire to measure women's knowledge in Hungary.